1999
DOI: 10.1111/j.1469-7793.1999.0525v.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of peristalsis by circumferential stretch of flat sheets of guinea‐pig ileum

Abstract: Segments of isolated guinea‐pig intestine, 12 mm long, were distended slowly by intraluminal fluid infusion or by mechanical stretch as either a tube or flat sheet. In all cases, at a constant threshold length, a sudden, large amplitude contraction of the circular muscle occurred orally, corresponding to the initiation of peristalsis. Circumferential stretch of flat sheet preparations evoked graded contractions of the longitudinal muscle (the ‘preparatory phase’), which were maintained during circular muscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 48 publications
6
80
1
Order By: Relevance
“…This contrasts with studies of ascending excitatory reflexes, which have found that such reflexes are graded according to the magnitude of the stimulus (Tonini et al 1996;Spencer et al 1999b). By contrast, the peristaltic reflex evoked in vitro by stretching the intestinal wall is an all-or-nothing phenomenon that is typically not preceded by a graded contraction of the circular muscle (Brookes et al 1999). In both the present study (Fig.…”
Section: Properties Of the Ascending Excitatory Pathwaycontrasting
confidence: 53%
See 1 more Smart Citation
“…This contrasts with studies of ascending excitatory reflexes, which have found that such reflexes are graded according to the magnitude of the stimulus (Tonini et al 1996;Spencer et al 1999b). By contrast, the peristaltic reflex evoked in vitro by stretching the intestinal wall is an all-or-nothing phenomenon that is typically not preceded by a graded contraction of the circular muscle (Brookes et al 1999). In both the present study (Fig.…”
Section: Properties Of the Ascending Excitatory Pathwaycontrasting
confidence: 53%
“…The output of the intrinsic sensory neurons to local motor neurons also includes slow EPSPs. Thus, motor neurons near the recording balloon will be tonically excited and primed to produce an all-or-nothing propulsive contraction in the same way that the oral end of a slowly distended segment of ileum is primed to produce a similar contraction with no graded pre-contraction (Brookes et al 1999).…”
Section: Properties Of the Ascending Excitatory Pathwaymentioning
confidence: 99%
“…These neighboring cells could then be activated by any of a number of proposed mechanotransduction mechanisms, including mechanosensitive ion channels, membrane-bound enzymes, or modulation of their cytoskeleton (Hill et al 2001). Evidence for all these mechanisms working in vascular and enteric SM exists (Brookes et al 1999;Farrugia et al 1999;Phillips and Powley 2000). Therefore, selective innervation of SMB MHC-rich cells that shorten quickly could, via stretch-activated mechanotransduction, activate neighboring cells, resulting in more rapid tissue activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is thought that stretch receptors are activated which can reinforce the gastrocolic reflex, causing an increase in motility of the gastrointestinal tract. 21 Also activation of the parasympathetic nervous system, which is highly involved in a Also subjects who did not complete the 10-week period, answered this question.…”
Section: Effects Of Massage On Colonic Function In Scimentioning
confidence: 99%